FREQUENCY OF TET2 GENE MUTATION IN MYELOPROLIFERATIVE NEOPLASMS - Syed Owais Ali (Army Medical College Rawalpindi, 2021)
Objective: To determine the frequency of Ten-Eleven-Translocation-2 (TET2) gene mutation in Myeloproliferative Neoplasms (MPNs) and to generate a local data for evaluation of disease behavior in ten-eleven-translocation-2 positive and negative Patients.